Design and Analysis of Asymmetric Capsule-Shaped Metallic Cavities for Unidirectional Waveguide Coupling - Baifu Zhang; Haifeng Hu; Hao Wang; Cheng Han; Zhe Shen; Ji Xu; Ming Sun; Li Li (IEEE Photonics Journal)
We propose and numerically investigate a novel asymmetric capsule-shaped metallic cavity (ACMC) structure for unidirectional waveguide coupling. By introducing cylindrical facets at cavity ends with different radius, asymmetric resonant mode is confined inside the cavity so that the evanescent energy can be unevenly coupled into the two directions of the waveguide underneath the cavity. We conduct three-dimensional finite-difference time-domain simulations and demonstrate the effectiveness of the proposed ACMC-based unidirectional waveguide coupling. Besides, by modifying suitable geometry of the proposed structure, the extinction ratio and coupling efficiencies of both directions of the waveguide can be flexibly designed, resulting in unequal coupling of optical energy. In addition, the dependence of the waveguide-coupling properties on ACMC geometry is also numerically investigated in this paper.